Tantangan Untuk Mengobati Hipoglikemia Bagi Pasien Lanjut Usia Diabetes Dalam Praktek Klinis Sehari-hari - Rochmah, Izzah; Erwan, Nabila; Mumtaza, Hilya (Jurnal Klinik dan Riset Kesehatan, 2023)
Background: Hypoglycemia is an acute complication that often occurs in daily clinical practice. The incidence of hypoglycemia is increased, one of which is by age factors and the use of insulin. Case Presentation: A 66-years old Indonesian woman with obesity (BMI=35.2 kg/m2) came to Emergency Department (ED) with decreased of consciousness due to a skipped meal after a prandial insulin injection with errors in calculating insulin dose. She had Diabetes Mellitus type 2 since 10 years ago and got insulin prescription since last year. The random blood sugar (RBG) was 27 mg/dl. Patient was administered intravenous D40% 75ml and the symptoms was improved. Patient was diagnosed this patient with severe hypoglycemia. During hospitalization, patient’s blood sugar had fluctuation in 2 days consecutive mornings and began to stable in day 3 on ward. When the patient discharged, we prescribed 24U basal insulin given before bed if the RBG level >200mg/dl. Discussion: In older population, the neuroglycopenic symptoms, such as lethargy, dizziness, and delirium appear in higher BG level than the autonomic symptoms. The disproportion of demand and supply of blood glucose in the brain causes the neuroglycopenic symptoms. In addition, those signs are also likely to be misinterpreted as signs of stroke, dementia, or vision problems. This cycle of misidiagnosed and the tendency of neuroglypenic symptoms lead the older population into hypoglycemia unawareness. Conclusion: Hypoglycemia unawareness is one of the warning signs of the severity of Diabetes Mellitus type 2 caused by multiple factors which has high prevalence in the elderly. Therefore, particular management is needed in this population by selecting the suitable glucose-lowering agent considering individualized patient preferences rather than focusing on the glycemic target.